Salient Features of Al-Maturidi’s Theory of Knowledge - Ishak, Adila (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Salient Features of Al-Maturidi’s Theory of Knowledge